Lentiviral tracking of vascular differentiation in bone marrow progenitor cells - Schmeckpeper, J.; Ikeda, Y.; Kumar, A.; Metharom, Pat; Russell, S.; Caplice, N. (Elsevier Ltd, 2009)
Lentiviral vectors encoding for identifiable marker genes controlled by lineage-specific promoters can be used to track differentiation of bone marrow progenitors into endothelial cells and/or smooth muscle cells. Human VE-Cadherin and Smoothelin-B promoters were cloned into a self-inactivating lentiviral vector (HR-VECad and HR-SMTHB) and used to drive expression of green fluorescent protein (eGFP). These constructs demonstrated specific promoter activity in mature endothelial and smooth muscle cells respectively in vitro. Lin− bone marrow progenitor cells (Lin− BMCs) in culture were used to test vector ability to track vascular differentiation. HR-VECad transduced Lin− BMCs were plated on collagen-coated slides and grown in endothelial media, while HR-SMTHB transduced Lin− BMCs were cultured on fibronectin-coated slides and grown in smooth muscle media. For in vivo differentiation assessment, lentiviral transduced Lin− BMCs resuspended in Matrigel were injected subcutaneously into C57BL/6J mice. Explants were evaluated for eGFP expression. Lin− BMCs grown in endothelial differentiation media produced groups of polygonal endothelial-like cells by days 16–21. When transduced with HR-VECad vector, these expressed eGFP in distinct cells within the colony by days 18–21, and coexpressed VE-Cadherin and eNOS. Lin− BMCs grown in smooth muscle differentiation media produced spindle-shaped cells between days 10–14 in culture. When transduced with the HR-SMTHB vector, these cells showed eGFP expression at ∼12 days, which increased over time and coexpressed αSMA, calponin and myosin heavy chain. Within Matrigel plugs containing HR-VECad transduced cells, eGFP+ constituted 0.4±0.2% of total cells. In contrast, within Matrigel plugs containing HR-SMTHB transduced cells, eGFP+ cells constituted 0.2±0.1% of total cells. These data demonstrate the feasibility of selectively marking BMC populations for cell fate determination.